THE RELATIONSHIP BETWEEN CUSTOMER SATISFACTION AND INTERNAL SERVICE QUALITY FROM AN INTERNAL MARKETING PERSPECTIVE AND AN APPLICATION IN THE BANKING SECTOR - Onurlu, Özlen; Karataş, Suna (International Journal of Research -GRANTHAALAYAH, 2016)
In a highly competitive environment, the meeting of customer demands and expectations in an effective way is highly crucial for companies that want to have a competitive advantage and to keep on existing in the long run. The main objective of companies is making profit in a sustainable way and this is possible by assuring customer satisfaction. The quality of the services that companies offer their customers is closely related with the performance of the employees. This has made it necessary that marketing activities for employee satisfaction be developed prior to customer satisfaction. Feeling more motivated, workers start working more eagerly as a result of these marketing activities which are called internal marketing. So, companies make their profitability sustainable by means of keeping their customers satisfied and loyal. The aim of this paper is to investigate the relationship between internal marketing activities applied to employees and employee motivations.